In Vitro and In Vivo Cytotoxicities and Antileishmanial Activities of Thymol and Hemisynthetic Derivatives (2005)
ABSTRACT: The in vitro and in vivo antileishmanial and cytotoxic activities of thymol and structural derivatives in comparison to those of Glucantime were studied. The results showed here suggest that thymol and hemisynthetic derivatives have promising antileishmanial potential and could be considered as new lead structures in the search for novel antileishmanial drugs.